Serving multiple ‘masters’: Evidence from the loan decisions of a publicly listed state-owned bank around a massive economic stimulus programme - Yuan, Hongqi; Zhou, Yiyuan; Zou, Hong (Journal of Corporate Finance, 2022)
Using China's 2008 four-trillion-yuan economic stimulus as a setting and proprietary loan data, we study how a large publicly listed state-owned bank responds to the government's countercyclical financing initiative while trying to meet the expectations of bank regulators and public investors. We find that the bank exhibited little changes in the process of setting internal credit ratings of borrowers, and internal ratings remain a valid, albeit weaker, predictor of interest rates in the stimulus period. Interest rates also remain a valid predictor of loan delinquency in the stimulus period. Evidence from analyzing unlisted borrowers is broadly similar. Overall, there is no systematic evidence that loan decisions of the state-owned bank are severely compromised in the stimulus period. The study adds to the limited understanding of how partially privatized state-owned banks balance different objectives in managing credit risk and is relevant to the longstanding debate over the roles of state-owned banks.